2001
DOI: 10.1037/1528-3542.1.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual asymmetries reflect developmental changes in the neuropsychological mechanisms of emotion recognition.

Abstract: To study how perceptual asymmetries in the recognition of emotion reflect developmental changes in processing affective information, a fused rhyming dichotic word test with positive, negative, and neutral stimuli was administered to adults and children. Results suggested that the hemisphere in which affective information is initially processed affects the strength of perceptual asymmetry and that children's perceptual processing of emotional information is constrained by limited computational resources. Anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…On this view, the condition in which negative stimuli were presented to the RH was predicted to lead to a computational overload, resulting in increased LH involvement in child participants. Other studies utilizing more complex stimuli, such as linguistic prosody, have shown that activation of multiple specialized systems within the same hemisphere may also result in a processing advantage for the opposite hemisphere, or in bilateral processing (e.g., Banich & Belger, 1990; Pollak & Wismer Fries, 2001; Mitchell, 2006). However, as affective prosody is commonly examined within the linguistic context, the processing of such stimuli including both affective content linked to RH processes, and linguistic content associated with LH processes, would inevitably result in more bilateral processing than would be the case for non-linguistic emotion.…”
Section: Discussionmentioning
confidence: 99%
“…On this view, the condition in which negative stimuli were presented to the RH was predicted to lead to a computational overload, resulting in increased LH involvement in child participants. Other studies utilizing more complex stimuli, such as linguistic prosody, have shown that activation of multiple specialized systems within the same hemisphere may also result in a processing advantage for the opposite hemisphere, or in bilateral processing (e.g., Banich & Belger, 1990; Pollak & Wismer Fries, 2001; Mitchell, 2006). However, as affective prosody is commonly examined within the linguistic context, the processing of such stimuli including both affective content linked to RH processes, and linguistic content associated with LH processes, would inevitably result in more bilateral processing than would be the case for non-linguistic emotion.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the right hemisphere model of ADHD demonstrating that abnormalities in the right hemisphere are indeed characteristic of ADHD and they account for various symptoms presented by this disorder (Aman, Roberts, & Pennington, 1998, Sandson, Bachna, & Morin, 2000, such as inattention, slower reaction times, visuospatial problems and poor social skills (Garcia-Sanchez, EstevezGonzalez, Suarez-Romero, & Junque, 1997;Stefanatos & Wasserstein, 2001). Behavioral and neurological studies with healthy and brain damaged subjects, has established that emotion recognition involves right hemisphere parietotemporal systems (Borod et al, 1998;Gainotti, 2000;Indersmitten & Gur, 2003;Pollak & Wismer Fries, 2001) and that this process does not emphasize higher order executive functions (Barkley, 1997;Gainotti, 2001).…”
Section: Emotion Recognitionmentioning
confidence: 98%
“…Dysfunction of the right hemisphere causes deficiencies in attentional deployment and in processing of emotional cues (Heilman, Voeller, & Nadeau, 1991;Pollak & Wismer Fries, 2001). Research shows that a depletion of norepinephrine exists in ADHD (Shaywitz & Shaywitz, 1988), and that these norepinephrine depleted pathways act on the posterior-right-hemisphere (Pennington, 1991), putting subjects with ADHD at risk for impairments in the ability to evaluate affective stimuli and sustain attention (Shapiro et al, 1993).…”
Section: Emotional Competence and Social Skillsmentioning
confidence: 98%
“…Most prior DL studies examining emotion processing have used affectively charged words, or words spoken with prosodic inflection (see, Borod, Pick & Hall, 2000; Pollak & Wismer Fries, 2001; Shipley‐Brown, Dingwall, Berlin, Yeni‐Komshian & Gordon‐Salant, 1988; Van Strien & Heijt, 1995; Van Strien & Morpurgo, 1992) as stimuli. Since receptive language abilities typically are left‐lateralized (in right‐handed individuals), linguistic stimuli may have an unequal effect on inference of affective processing across the hemispheres because the eliciting stimuli are both affective and linguistic.…”
Section: Introductionmentioning
confidence: 99%